An Examination Of The Practical Implementation Of The Neo Mabims Criteria In The Determination Of The New Islamic Month In Indonesia. - Hikam, Farras Fathan; Rofiuddin, Ahmad Adib; Rahman, Mohammad Zulfaiz Akbar bin Abdul (Journal of Southeast Asian Islam and Society, 2025)
The Ministers of Religious Affairs of Brunei Darussalam, Indonesia, Malaysia, and Singapore (MABIMS) have reached a consensus to modify the existing criteria (criteria [2, 3, 8]) by employing the recently developed MABIMS criteria (criteria [3Â° - 6,4Â°]) as the foundation for determining the onset of the Hijri month. Following its implementation in 2022, the Neo MABIMS criteria have encountered numerous challenges and intricate implementation challenges. The application of these criteria has been met with both advantages and disadvantages. This study aims to analyze the application of the Neo MABIMS criteria by the Ministry of Religious Affairs in determining the beginning of the Hijri month in Indonesia. The study will assess the effectiveness of the policy in harmonizing differences and addressing implementation challenges. This research explores the dynamics of applying the new criteria, including technical and social aspects that affect the implementation process in the field. The research method employed is qualitative-descriptive with a documentary research approach. The analysis technique entailed three stages: data presentation, data condensation, and interpretation. The findings indicate that the implementation of these criteria has been hindered by persistent differences in determining the start of the Hijri month in Indonesia. The utilization of the Neo MABIMS criteria is characterized by inconsistency, which is a substantial impediment to this process. This finding underscores the necessity for a comprehensive evaluation of the consistency and application of the Neo MABIMS criteria, particularly in addressing rukyat reports that deviate from the established astronomical parameters.